2001
DOI: 10.1128/jb.183.24.7126-7134.2001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of the Pseudomonas aeruginosa PA14 rpoN Gene in Pathogenicity in Plants, Nematodes, Insects, and Mice

Abstract: We cloned the rpoN (ntrA, glnF) gene encoding the alternate sigma factor 54 from the opportunistic multihost pathogen Pseudomonas aeruginosa strain PA14. A marker exchange protocol was used to construct the PA14 rpoN insertional mutation rpoN::Gen r . PA14 rpoN::Gen r synthesized reduced levels of pyocyanin and displayed a variety of phenotypes typical of rpoN mutants, including a lack of motility and the failure to grow on nitrate, glutamate, or histidine as the sole nitrogen source. Compared to wild-type PA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 67 publications
2
87
0
2
Order By: Relevance
“…argues strongly that hutC and hutD form a single hutCD transcription unit (175). It is interesting that like the Hut systems from enteric bacteria (46,84), all of the hut operons of P. fluorescens (and perhaps other pseudomonads [52,64]) can be transcribed by the "housekeeping" RNA polymerase, which carries 70 as its promoter recognition subunit (175,176). However, the hutU-G operon of P. fluorescens can also be transcribed from a promoter that is recognized by the unusual RNA polymerase that carries 54 (also known as N ) as its promoter recognition subunit (175,176), as described in more detail in the section on regulation (see below).…”
Section: Pseudomonadsmentioning
confidence: 99%
“…argues strongly that hutC and hutD form a single hutCD transcription unit (175). It is interesting that like the Hut systems from enteric bacteria (46,84), all of the hut operons of P. fluorescens (and perhaps other pseudomonads [52,64]) can be transcribed by the "housekeeping" RNA polymerase, which carries 70 as its promoter recognition subunit (175,176). However, the hutU-G operon of P. fluorescens can also be transcribed from a promoter that is recognized by the unusual RNA polymerase that carries 54 (also known as N ) as its promoter recognition subunit (175,176), as described in more detail in the section on regulation (see below).…”
Section: Pseudomonadsmentioning
confidence: 99%
“…For instance, the sigma factor RpoS is a positive regulator of psl gene expression in P. aeruginosa (66), yet inactivation of rpoS has been correlated with more-substantial biofilm biomass accumulation compared to that of the wild type (59). Similarly, P. aeruginosa rpoN mutants are capable of forming biofilms but are impaired in attachment while demonstrating in-creased production of sadB, which is essential for attachment (20,57,143,151). SadC has been demonstrated to contribute to attachment.…”
Section: Is Attachment An Indicator For Biofilm Formation?mentioning
confidence: 99%
“…Nevertheless, several genes that have been identified as QS regulated, including rhlA, rpoS, sadA, and those in the denitrification pathway, have been shown to be important in P. aeruginosa biofilm development, maintenance, and dispersion [10,59,68,69]. A recent study of P. aeruginosa biofilms in the mouse thermal injury model suggested that QS was not important in the formation of biofilms in acute infection [70]; however, several previous studies have clearly demonstrated a role for QS in this model [71][72][73][74]. Further investigation is clearly needed to precisely define the role of QS in both in vitro and in vivo biofilm development.…”
Section: Introductionmentioning
confidence: 96%
“…Numerous models of infection, including plant, invertebrate, and animal models, have supported the premise that QS contributes to P. aeruginosa pathogenesis [71][72][73][74][93][94][95][96][97][98][99][100][101]. In animal models of lung pathogenesis, including the mouse model of acute pneumonia, the mouse model of chronic lung infection, and the rat chronic lung infection model, lasR, lasI, and rhlI have been demonstrated to be required for virulence [73,93,[102][103][104][105].…”
Section: Introductionmentioning
confidence: 99%